Enlivening secondary history : 50 classroom activities for teachers and pupils - Davies, Peter, 1966- (Routledge, 2012)
"Enlivening Secondary History is the ideal handbook for busy history teachers who want to do something different in their classrooms, but have little time to plan and organise their lessons. Featuring tried-and-tested practical ideas complete with relevant exemplars and step-by-step advice, this best-selling book is a compendium of creative activities to enhance your lessons For the 11-19 age range, each activity includes links to important topics including the Crusades, the Reformation, the World Wars, the Russian Revolution and many more. All the ideas are explained in a clear, user-friendly style, with a breakdown of the time and resources needed for each one. Featuring a brand new expanded section about teaching history with multimedia, this book also covers: - Visuals - picturing the past - Numerical data - adding interest - Concepts - making them real - Primary texts - bringing them alive. Written by practitioners for practitioners, Enlivening Secondary History helps teachers to bring history alive in an imaginative ways. It will be an indispensable guide for both experienced and student teachers"--